The Seek & Share Resources Tool: Measuring a Learning Practice of Making. Issue 2 (13th September 2022) - White, Annie M.; Saplan, Kailea; Wardrip, Peter S.; Bank, Alison; Akiva, Thomas; Brahms, Lisa
Abstract: The maker movement has grown rapidly in educational contexts during the past decade. The field now needs valid, reliable measurement tools to capture learning that occurs in maker-based activities. In this study, facilitators and researchers from five organizations engaged in a codesign process to develop a tool measuring how learners seek and share resources while making. We describe our process of collaboratively developing, testing, and revising the Seek & Share Resources Tool and the coding protocol with strong validity. Two researchers coded 50 videos depicting learners ages 0-14 engaging in diverse maker-based activities yielding high inter-rater reliability for the tool. The Seek & Share Resources Tool offers a valid, reliable measure of learning behavior in making and our process may be replicated in future research of rigorous measurement tool design.